The Prevalence and Pattern of Non-Medical Use of Prescription Drugs in Abakaliki, Southeast, Nigeria - Anozie, Okechukwu B.; Johnbosco, Nwafor I.; Esike, Chidi U.; Ukaegbe, Chukwuemeka I.; Enyanwuma, Ifeanyi E.; Nwokporo, Ifediri E.; Ewah, Richard L. (International Journal of Innovative Research in Medical Science, 2019)
Introduction: The growing of non-medical use of prescription drugs is a global health problem and it has emerged as a particularly dangerous health-behavior among young people. However studies assessing misuse among people in Abakaliki are non-existent. Aim: To determine the prevalence and pattern of non-medical use of prescription drugs in Abakaliki. Materials and method: This was a cross-sectional study that involved 420 participants. The respondents completed an anonymous, self-administered questionnaire assessing past-year prevalence and pattern of non-medical use of five classes of prescription drugs. The data was analyzed using SPSS version 20. Results: The prevalence of non-medical use of prescription drugs in this study was 38.3%. The mean age of the participants was 22.2 ± 3.8 years with majority of them (38.3%) being within the 19-25 years age bracket. The majority of participants were males (52.1%) whereas female accounted for 47.9% of the respondents. Pain medications such as tramadol, codeine and morphine accounted for majority (73.8%) of unprescribed medication abused by the respondents. This is followed by other medications such as ibuprofen which was 45%. Sleeping medications and stimulants accounted for 28.3% and 27.4% of unprescribed drugs respectively. Similarly, pain medication accounted for majority (74.8%) of prescribed medicines used by the participants for non medicinal purposes. The least abused class of drugs in the prescribed category were sedative/anxiety medications which accounted for just over 18%. To relax or relieve tension is the most common reasons (20.5%) for use of drugs for non medical purposes reported in this study. Other reasons include to improve concentration (16.7%), to get high (10.7%) and for recreation (6.9%). Conclusion: This study shows high prevalence of non medical use of prescription drugs among our study participants in Abakaliki.